2002
DOI: 10.1042/bst0300722
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evidence for the role of a ferric reductase in iron transport

Abstract: Duodenal cytochrome b (Dcytb) is a haem protein similar to the cytochrome b561 protein family. Dcytb is highly expressed in duodenal brush-border membrane and is implicated in dietary iron absorption by reducing dietary ferric iron to the ferrous form for transport via Nramp2/DCT1 (divalent-cation transporter 1)/DMT1 (divalent metal-transporter 1). The protein is expressed in other tissues and may account for ferric reductase activity at other sites in the body.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 4 publications
0
24
0
2
Order By: Relevance
“…The Nramp2 mRNA contains IREs and the expression of Nramp2 is regulated post-transcriptionally by the iron level in the body. Defects in Nramp2 (mk mouse and Belgrade rat) lead to the impaired transport of iron and the defective endosomal transport of iron (Andrews 2002;McKie et al 2002). These results indicated that Nramp2 is also involved in the transport of ferrous ion across endosomal membrane into the cytoplasm after the transferrin-iron is released from transferrin in endosomes and reduced by ferrireductase.…”
Section: New Members Involved In the Regulation Of Intracellular Levementioning
confidence: 65%
See 2 more Smart Citations
“…The Nramp2 mRNA contains IREs and the expression of Nramp2 is regulated post-transcriptionally by the iron level in the body. Defects in Nramp2 (mk mouse and Belgrade rat) lead to the impaired transport of iron and the defective endosomal transport of iron (Andrews 2002;McKie et al 2002). These results indicated that Nramp2 is also involved in the transport of ferrous ion across endosomal membrane into the cytoplasm after the transferrin-iron is released from transferrin in endosomes and reduced by ferrireductase.…”
Section: New Members Involved In the Regulation Of Intracellular Levementioning
confidence: 65%
“…After the absorption of iron by intestinal Nramp2, the transport of iron across the basolateral membrane to the portal vein occurs. An ironregulated transporter, IREG1, specially expressed in the duodenal mucosa has been cloned, and functions in the stimulation of iron efflux from the cells (McKie et al 2002). The expression of IREG1 is increased dependent on the increase in iron absorption and the 5´-uncoding region of IREG1 mRNA contains an IRE.…”
Section: New Members Involved In the Regulation Of Intracellular Levementioning
confidence: 99%
See 1 more Smart Citation
“…However, the vitamin has other important, non-antioxidant biological functions [16,17], of which some are related to its ability to reduce ferric (Fe 3+ ) to ferrous (Fe 2+ ) iron. AA promotes intestinal absorption of dietary non-haem Fe 2+ iron through the divalent metal transporter 1 [18] and increases the activity of Fe 2+ -dependent prolyl hydroxylases that participate in the synthesis of collagen and carnitine [19,20]. The ability of AA to reduce ferric to ferrous iron may, Vitamin C, DNA damage and iron homeostasis 5 however, have deleterious consequences.…”
Section: Introductionmentioning
confidence: 99%
“…(72). The cytoplasmic Fe(II) can efflux from the enterocyte at the basolateral surface via the Fe(II) permease Fpn.…”
Section: Ferrireductases and Ferroxidases Are The Iron Metabolic Pathwaymentioning
confidence: 99%